2005
DOI: 10.1071/mf04179
|View full text |Cite
|
Sign up to set email alerts
|

Can otolith chemistry be used for identifying essential seagrass habitats for juvenile spotted seatrout, Cynoscion nebulosus, in Chesapeake Bay?

Abstract: We investigated the variability of otolith chemistry in juvenile spotted seatrout from Chesapeake Bay seagrass habitats in 1998 and 2001, to assess whether otolith elemental and isotopic composition could be used to identify the most essential seagrass habitats for those juvenile fish. Otolith chemistry (Ca, Mn, Sr, Ba, and La; δ 13 C, δ 18 O) of juvenile fish collected in the five major seagrass habitats (Potomac, Rappahannock, York, Island, and Pocomoke Sound) showed significant variability within and betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 27 publications
4
62
0
Order By: Relevance
“…Sites within locations were located within approximately 5 to 10 km of each other. Such small-scale differences have also been identified in other studies (Thorrold et al 1998a,b, Hamer et al 2003, Dorval et al 2005. It is possible that these small-scale differences observed in Menidia menidia otoliths reflect small-scale differences in water chemistry among sites.…”
Section: Spatial Differencessupporting
confidence: 78%
See 2 more Smart Citations
“…Sites within locations were located within approximately 5 to 10 km of each other. Such small-scale differences have also been identified in other studies (Thorrold et al 1998a,b, Hamer et al 2003, Dorval et al 2005. It is possible that these small-scale differences observed in Menidia menidia otoliths reflect small-scale differences in water chemistry among sites.…”
Section: Spatial Differencessupporting
confidence: 78%
“…Differences in elemental signatures have been identified in fish from different estuaries (Thorrold et al 1998b, Gillanders 2002b, rivers (Walther et al 2008), reef habitats (Patterson et al 2004), seagrass beds (Dorval et al 2005), coastal areas (Campana et al 1999, Warner et al 2005, and oceanic regions (Ashford et al 2005), thus supporting the idea that otoliths can be used as natural tags. The spatial scales at which habitats can be discriminated, however, is still being investigated and will likely differ among systems (see review Gillanders 2002b).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…in recent years biologists have explored stable isotope relationships to these variables and have found, for instance, that δ 15 N and δ 87 sr are enriched in fish moving from estuarine to deep water habitats, and δ 13 C is enriched in seagrass habitats (Hobson, 1999: 320-321;Nagelkerken and van der Velde, 2004 Hanson, Koenig, and Zdanowicz, 2004;Dorval et al, 2004;Kennedy et al, 2005;Martin and Thorrold, 2005;Surge and Walker, 2005;Comyns et al, 2008;Fodrie and Herzka, 2008;Fodrie et al, 2010;cf. Chittaro et al, 2005cf.…”
Section: Habitat Analysismentioning
confidence: 99%
“…Representative case studies of Daverat et al (2005), Tzeng et al (2005), McCulloch et al (2005), Dorval et al (2005) and Hobbs et al (2005) demonstrated the utility of otolith chemistry in tracking movements and/or habitat shifts throughout the life history of fish, which, in turn, can be used to infer stock structure and population connectivity (Fowler et al 2005;Stransky et al 2005). Similarly, Gillanders and Joyce (2005) used otolith chemistry to differentiate aquaculture and wild-harvest yellowtail kingfish (Seriola lalandi), whereas Niva et al (2005) examined the effectiveness of alizarin-red-stained otoliths as a cost-effective mass-marking tool.…”
Section: Chemical Composition and Applications To Climate Ecology Anmentioning
confidence: 99%